Peculiarities of slang usage in media discourse - Haiduk, Martha (Видавництво Львівської політехніки, 2017)
The article deals with the features of slang usage in modern media discourse. The analysis of its specific textual characteristics has been carried out.
Keywords: slang; media discourse; discourse analysis